2016
DOI: 10.2298/vsp150208075b
|View full text |Cite
|
Sign up to set email alerts
|

Upper extremity function and quality of life in patients with breast cancer related lymphedema

Abstract: Physical disability in patients with breast cancer-related lymphedema influences quality of life more than mental health. Upper limb function has a significant impact on quality of life, not only on the physical, but also on the mental component. The presence of breast-cancer-related lymphedema certainly affects upper limb function and quality of life, but in this study no significant correlation between the size of edema and quality of life was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…9,10 One potential effect of BCRL is impairment in activities of daily living (ADLs), which include bathing, dressing, toileting, transferring, continence, and feeding. [11][12][13][14][15][16] ADLs are sets of essential activities that enable a person to live a minimally independent life; thus, they are important indicators for physical function. With impairments in ADLs, quality of life and independence of living diminish because one cannot function as an independent individual when basic daily living activities cannot be accomplished.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 One potential effect of BCRL is impairment in activities of daily living (ADLs), which include bathing, dressing, toileting, transferring, continence, and feeding. [11][12][13][14][15][16] ADLs are sets of essential activities that enable a person to live a minimally independent life; thus, they are important indicators for physical function. With impairments in ADLs, quality of life and independence of living diminish because one cannot function as an independent individual when basic daily living activities cannot be accomplished.…”
Section: Introductionmentioning
confidence: 99%
“…28 Cross-sectional models showed that upper extremity dysfunction was correlated with HRQoL in patient population. 29,30 Our findings demonstrated that HRQoL of participants with sleep disturbance were significantly lower than those of participants without sleep disturbance. Negative correlation was found between the HRQoL and AIS scores of all participants.…”
Section: Discussionmentioning
confidence: 62%
“…Studies examining social support concerns in women with BCRL report that women continue to experience concerns of lack of privacy, social support, and relationships suggesting the need for social support interventions [30][31][32][33][34]. Reports were mixed regarding associations between the presence of BCRL and QOL, with some studies reporting that self-reported BCRL symptoms are more indicative of QOL scores, while objective measures of BCRL are less predictive of QOL scores [36][37][38][39][40]. Differences in study designs, underpowered samples, and a lack of disease-specific instruments to psychosocial impact of BCRL, including QOL [8], likely account for these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, another group found associations between older age and poorer QOL among those with BCRL (N = 201) [9•]. In contrast, three studies reported the presence of BCRL was not associated with QOL [38][39][40]. Differences between study designs, including sample characteristics (e.g., age of participants and diseasespecific exclusion criteria) [39] and instruments (SF-12, SF-36, and FACT-B) used to assess QOL, may account for these findings.…”
Section: Psychological Health Factorsmentioning
confidence: 99%